Clinical characteristics of pulmonary Mycobacterium lentiflavum disease in adult patients. (February 2018) - Yagi, Kazuma; Morimoto, Kozo; Ishii, Makoto; Namkoong, Ho; Okamori, Satoshi; Asakura, Takanori; Suzuki, Shoji; Asami, Takahiro; Uwamino, Yoshifumi; Funatsu, Yohei; Fujiwara, Hiroshi; Kamata, Hirofumi; et al.
Highlights: Mycobacterium lentiflavum is often associated with cervical lymphadenitis in young children. The clinical features of pulmonary M. lentiflavum infection in adults are unknown. Pulmonary M. lentiflavum disease affects middle-aged and elderly female adults. The radiological pattern mainly shows a nodular/bronchiectatic pattern. No cases in this study, including those identified in a literature review, showed an aggressive clinical course. Abstract: Background: Mycobacterium lentiflavum is a slow-growing non-tuberculous Mycobacterium that is often associated with an immunocompromised state and cervical lymphadenitis in young children. However, little is known about the clinical importance of pulmonary infection with M. lentiflavum in adults. Methods: The medical records of all adults who met the diagnostic criteria of pulmonary M. lentiflavum disease at Keio University Hospital and Fukujuji Hospital from 2001 to 2015 were reviewed. In addition, the PubMed database was searched to identify further reported cases in non-HIV adults. Results: Five cases of pulmonary M. lentiflavum disease were identified in the medical records search and 11 additional cases were identified in the literature review. Eleven of the total 16 cases were female, and 15 of 16 cases showed a nodular/bronchiectatic pattern on chest computed tomography imaging. No cases showed an aggressive clinical course of pulmonary M. lentiflavum disease, although one patient died of an exacerbation of underlying vasculitis and bacterial pneumonia. Conclusions: The clinical characteristics of pulmonary M. lentiflavum disease in adult patients were identified. This disease mainly affects females, displays a nodular/bronchiectatic pattern on chest computed tomography imaging, and does not demonstrate an aggressive clinical course. Further larger studies are needed to reveal detailed clinical features.